Respuesta :

Answer:

Step-by-step explanation:

BDC=95

Answer:

[tex] m\angle BDC = 95\degree [/tex]

Step-by-step explanation:

[tex] In\: \triangle ACD\: \&\:\triangle BDC[/tex]

[tex] m\angle A = m\angle B[/tex] (given)

[tex]\because m\angle A = 50\degree [/tex]

[tex]\therefore m\angle B = 50\degree [/tex]

[tex] m\angle ADC = m\angle BCD[/tex] (given)

[tex]\because m\angle ADC = 35\degree [/tex]

[tex]\therefore m\angle BCD= 35\degree [/tex]

[tex] In\: \triangle BDC[/tex]

[tex] m\angle BDC = 180\degree - (m\angle B+m\angle BCD) [/tex]

(By angle sum postulate of a triangle)

[tex] m\angle BDC = 180\degree - (50\degree +35\degree ) [/tex]

[tex] m\angle BDC = 180\degree - (50\degree +35\degree ) [/tex]

[tex] m\angle BDC = 180\degree - 85\degree [/tex]

[tex] m\angle BDC = 95\degree [/tex]